Private Attached Network Cloud Storage Using IOT - et. al., K.Kishore Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Building cloud computing environment using a low-cost systems based on the Raspberry Pi is very effective for use as a storage system in libraries and classrooms in schools and universities in developing countries where money is always an impediment. Weaved is used for remote access to set up Raspberry Pi from any device such as a smartphone. Numerous services are configured on the weave to control such as: SSH, HTTP, and VNC. Admin alone has access to private Cloud account. The administrator can provide various services to users through Weaved. This paper presents the results of an experimental preparation of low-cost computing environment using Raspberry Pi 3(Model B) and design analysis, in addition to a literature review of Raspberry Pi and a methodology applied. Our design will provide you with free data storage according to the requirements. In addition, give the freedom to use space and savings with strong control over the system